2014
DOI: 10.1515/hf-2013-0247
|View full text |Cite
|
Sign up to set email alerts
|

Hygric properties of Norway spruce and sycamore after incubation with two white rot fungi

Abstract: In this study, changes in the hygroscopic properties of two main wood species for violin making, Norway spruce and sycamore, after treatment with Physisporinus vitreus and Xylaria longipes were investigated. Swelling and moisture sorption capacity of wood at the growth ring scale were visually and quantitatively assessed by thermal neutron radiography analysis. It was demonstrated that the fungal treatment improved the dimensional stability of both Norway spruce and sycamore, but also increased their moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…2d, the peak in sorption hysteresis for wood is a result of scanning isotherms being used to calculate hysteresis, and the peak position changes with the RH from which . The absolute sorption hysteresis from literature data was evaluated from absorption and desorption isotherms from water saturated state (Ahlgren 1972;Fredriksson and Johansson 2016), between absorption and desorption from 94 to 95% RH (Gilani and Schwarze 2015;Gilani et al 2014;Kymäläinen et al 2015;Zillig 2009) and between absorption and desorption from 80% RH (Zillig 2009) desorption is initiated. Whether this is also the case for other biopolymeric materials remains to be investigated.…”
Section: Sorption Hysteresismentioning
confidence: 99%
“…2d, the peak in sorption hysteresis for wood is a result of scanning isotherms being used to calculate hysteresis, and the peak position changes with the RH from which . The absolute sorption hysteresis from literature data was evaluated from absorption and desorption isotherms from water saturated state (Ahlgren 1972;Fredriksson and Johansson 2016), between absorption and desorption from 94 to 95% RH (Gilani and Schwarze 2015;Gilani et al 2014;Kymäläinen et al 2015;Zillig 2009) and between absorption and desorption from 80% RH (Zillig 2009) desorption is initiated. Whether this is also the case for other biopolymeric materials remains to be investigated.…”
Section: Sorption Hysteresismentioning
confidence: 99%
“…5b). This means that not all the gained moisture during sorption is bound chemically to the cell walls, and thus does not affect the dimensional stability of wood [24]. Selective degradation of structural cell wall constituents by white rot fungi treatment can be another explanation for the observed behavior, as already evidenced with FT-IR spectroscopy [25].…”
Section: Hysteresis Of Moisture Exchange and Vibrational Propertiesmentioning
confidence: 62%
“…For this purpose, we have studied the influence of common traditional European varnish materials and coating build-ups on the sorption process of the underlying wood to understand how instruments react to changes in relative humidity. Neutron imaging is known as a convenient technique to investigate moisture content changes and liquid water transport in wood 2629 and its suitability to study the influence of coatings on the sorption dynamics has been demonstrated 30 . By using in-situ neutron imaging, we could non-destructively quantify and localize wood moisture gradient changes over time with a spatial resolution of several tens of micrometers (Fig.…”
Section: Introductionmentioning
confidence: 99%